2018
DOI: 10.1002/cptc.201800210
|View full text |Cite
|
Sign up to set email alerts
|

Selective Photocatalytic Carbon Dioxide Reduction by a Reduced Molybdenum‐Based Polyoxometalate Catalyst

Abstract: Currently, photochemical carbon dioxide reduction is a most sought‐after process as it involves the simultaneous removal of greenhouse CO2 gas and the production of useful products. In this study, we report the selective formation of formaldehyde in photochemical carbon dioxide reduction using a reduced polyoxometalate (POM) based catalyst. By simply tuning the redox state of the metal centre in the POM, we can obtain the more reduced product formaldehyde from carbon dioxide. As a result of the high MoV/MoVI r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 101 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…Surprisingly, an increase in the number of such reduced metal centres (Mo V /Mo VI ¼ 3) results in the generation of more reduced products like HCHO. 193 The most recent development in this direction has been achieved using a charge-stabilized dispersion of Mo 154 POM as a hollow spherical entity (Scheme 17). 194 The unique shape of the catalyst enables the catalytically produced HCOOH to be available in two forms: (i) in the external phase, accessible to the bulk reaction phase, and (ii) embedded inside the cavity.…”
Section: Polyoxometalate Catalysed Photochemical Co 2 Reduction Coupl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, an increase in the number of such reduced metal centres (Mo V /Mo VI ¼ 3) results in the generation of more reduced products like HCHO. 193 The most recent development in this direction has been achieved using a charge-stabilized dispersion of Mo 154 POM as a hollow spherical entity (Scheme 17). 194 The unique shape of the catalyst enables the catalytically produced HCOOH to be available in two forms: (i) in the external phase, accessible to the bulk reaction phase, and (ii) embedded inside the cavity.…”
Section: Polyoxometalate Catalysed Photochemical Co 2 Reduction Coupl...mentioning
confidence: 99%
“…Surprisingly, an increase in the number of such reduced metal centres (Mo V /Mo VI = 3) results in the generation of more reduced products like HCHO. 193…”
Section: Polyoxometalate Catalysed Photochemical Co2 Reduction Couple...mentioning
confidence: 99%
“…The irradiation of ultraviolet (UV) or near UV light can induce the charge transfer from oxygen to metal (OMCT), generating photoexcited POMs (POMs*). This active species, similar to the charge separation state in semiconductor photocatalysts, is highly reactive. POMs can serve as both oxidizing agents and reducing agents and can be used in various photocatalytic reactions. In recent years, some POMs have been found to have good activity in the photocatalytic degradation of organic pollutants, H 2 evolution, CO 2 reduction, etc.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In addition to rare examples of transition-metal (M)-substituted poly- oxotungstates, 13−16 reduced polyoxomolybdates [i.e., containing Mo(V) ions] emerged in 2019 as promising candidates. 17−19 Illustratively, {ε-Mo V 12 Mo VI 4 O 52 } reduces CO 2 into formaldehyde under ultraviolet (UV) light in homogeneous conditions 17 and the related {ε-PMo V 8 Mo VI 4 Zn 4 O 52 }, as the building unit of a POM-based metal−organic framework (POMOF), selectively reduces CO 2 into formate in heterogeneous conditions under visible light. 18 Two other families of solids made of reduced POM building units have been recently evidenced as heterogeneous photocatalysts for CO 2 RR.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There is thus an ever-growing incentive to develop efficient, selective, and recyclable dedicated heterogeneous catalysts for CO 2 photoreduction reaction (CO 2 RR) using visible light. Polyoxometalates (POMs) as soluble anionic metal oxide clusters of d-block transition metals in high oxidation states, typically W­(VI), Mo­(V,VI), or V­(IV,V), exhibit redox and acid–base properties and are particularly exploited in catalysis, either under homogeneous conditions , or immobilized in solid supports. In the hot field of solar energy conversion, although numerous studies have revealed their potentialities as catalysts for water splitting, there have been scarce reports on POMs for CO 2 RR. , In addition to rare examples of transition-metal (M)-substituted polyoxotungstates, reduced polyoxomolybdates [i.e., containing Mo­(V) ions] emerged in 2019 as promising candidates. Illustratively, {ε-Mo V 12 Mo VI 4 O 52 } reduces CO 2 into formaldehyde under ultraviolet (UV) light in homogeneous conditions and the related {ε-PMo V 8 Mo VI 4 Zn 4 O 52 }, as the building unit of a POM-based metal–organic framework (POMOF), selectively reduces CO 2 into formate in heterogeneous conditions under visible light . Two other families of solids made of reduced POM building units have been recently evidenced as heterogeneous photocatalysts for CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%